Single-Site Low-Flow Veno-Venous Extracorporeal Lung Support Does Not Influence Hemodynamic Monitoring by Transpulmonary Thermodilution. Issue 4 (July 2016) - Redwan, Bassam; Ziegeler, Stephan; Freermann, Stefan; Meemann, Thomas; Semik, Michael; Dickgerber, Nicolas; Fischer, Stefan
Abstract : The application of extracorporeal lung support (ECLS) in patients with acute respiratory distress syndrome is a well-established concept. In patients receiving ECLS therapy, hemodynamic monitoring is often required. However, less is known about the effect of ECLS on hemodynamic measurements. In the present work, the influence of single-site low-flow veno-venous ECLS (LFVV-ECLS) on hemodynamic monitoring by transpulmonary thermodilution (TPTD) was prospectively investigated. Five consecutive patients undergoing single-site LFVV-ECLS for severe hypercapnic respiratory failure were included in this study. For single-site LFVV-ECLS, a 22 Fr twin-port double-lumen cannula was inserted percutaneously into the right jugular vein. Hemodynamic monitoring was performed using the Pulse index Continuous Cardiac Output system. Before ECLS initiation, baseline measurements of cardiac index, systemic vascular resistance, mean arterial pressure, and extravascular lung water (EVLW) were performed. During the first 3 days of ECLS therapy, repeated hemodynamic measurements at different ECLS flow rates were performed. No significant differences were seen in hemodynamic measurements. With respect to EVLW, a significant decrease over the duration of ECLS therapy was observed. This study demonstrates that LFVV-ECLS does not interfere with TPTD. It needs to be further studied if these findings also apply to other ECLS modes.